The determinants of tourism revenue in Vietnam: A study with the spatial panel regression - Thao Thi Phuong Hoang (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
The Vietnamese government has been putting great effort into tourism development over these decades. The key strategies are to focus on regional linkages and to improve competitiveness by creating a fair, transparent, and dynamic governance environment. This research aims to investigate the determinants of tourism revenue in Vietnam in 2015 - 2019. The spatial panel regression method is employed for conducting the study. The study finds a spatial effect on tourism revenue in 63 provinces but it is a negative one. The number of tourists, the number of hotels, movement, and reducing time cost play an important role in improving tourism economic efficiency. Meanwhile, eliminating informal charges and improving proactive leadership raise a warning for policymakers due to their negative impact on Vietnam’s tourism revenue growth in the period 2015 - 2019. Based on the findings, this study contributes several policy recommendations.